NUSYUZ DALAM WACANA FIQIH DAN GENDER - Trigiyatno, Ali (MUWAZAH, 2010)
A valid marriage will bear the consequences of the rights and obligations of husband and wife. If each couple meet and fulfill what the obligations of each, are expected home will easily reach what is often presented as households that sakinah, mawaddah wa mercy. Nushuz is an attitude of ignoring the rights and obligations that each spouse feels aggrieved and persecuted. From the teachings of Islam has been anticipated by the various instructions and teachings for it not increasingly protracted. However, the conception nushuz sebagin understood by those impressed gender biased because it puts the woman or wife as the party that 'the accused'. Such a perspective is of course harm and discredit the position of women, so that a new perspective needs to be introduced in order to create gender relations of husband and wife are equal, just and humane